On the tropospheric zonal and meridional fluxes of moisture in relation to nor’westers in Bangladesh during the pre-monsoon season (MAUSAM, 2007)
Attempts have been made to study the zonal and meridional fluxes of moisture of the troposphere prior to the occurrence of nor’westers in Bangladesh during the pre-monsoon season. The study reveals that the westerly fluxes (positive) of moisture (WFM) dominate in the troposphere over Dhaka at 0000 UTC from 925 to 200 hPa level having maximum frequency of WFM from 61.68 to 96.26% in the layer from 925 to about 300 hPa level. The maximum WFM over Dhaka at 0000 UTC on the dates of occurrence of nor’westers may be more than 200 gm kg-1 × ms-1 in the lower troposphere and the maximum easterly (negative) fluxes of moisture (EFM) over Dhaka at 0000 UTC may be -128.3 gm kg-1 × ms-1 at 1000 hPa. In the upper troposphere the zonal fluxes of moisture (ZFM) become nil in most of the cases. The ZFM over Dhaka at 0000 UTC are mainly westerly and more westerly in the lower and middle troposphere on the dates of occurrence of nor’westers as compared to the fluxes on the dates of non-occurrence. The southerly fluxes (positive) of moisture (SFM) dominate in the troposphere over Dhaka at 0000 UTC from 1000 to 300 hPa level. The meridional fluxes of moisture (MFM) are mainly southerly and more southerly in the lower and middle troposphere on the dates of occurrence of nor’westers as compared to the dates of non-occurrence. In the upper troposphere the MFM become nil in most of the cases.The vertically integrated ZFM and MFM from 1000 to 100 hPa over Dhaka at 0000 UTC on the dates of occurrence of nor’westers in Bangladesh have been computed, compared and inference has been drawn. The present study also deals with the spatial distribution of the vertically integrated ZFM and MFM from 925 to 400 hPa level over Bangladesh and its surrounding areas. The range of the vertically integrated ZFM and MFM for the layer is about (2-12) × 105 and (3-14) × 105 kg × ms-1 respectively over Bangladesh in most of the cases.